Crescimento inicial de mogno africano (Khaya spp.) sob diferentes condições microclimáticas associadas à deficiência hídrica - Santos Neto, Alcides Pereira (2014)
The forest sector is challenged to perform plantations of new species with timber potential in order to meet the growing demand for quality wood and provide an alternative to illegal use of native trees. In this regard it is noteworthy species of the genus Khaya, popularly known as african mahogany. In Brazil, the most cultivated species in this genus are Khaya ivorensis A. Chev., K. senegalensis A. Juss. and K. anthotheca (Welw.) C. DC. However, few studies have been developed with this genre, there is a need to point climate preferences, generating important for the successful implementation of stands with african mahogany information. Thus, the present study aimed to compare the growth of three different species of African mahogany (K. ivorensis, K. senegalensis and K. anthotheca) subjected to different microclimatic conditions and water availability in the substrate. The study was conducted in the experimental area of the Department of Forest and Wood Sciences Center of Agricultural Sciences, Federal University of Espírito Santo. The seedlings were planted in pots of 12 l, which were allocated inside the house air-conditioned greenhouse with controlled temperature, humidity and available water in the substrate. After 88 days of trial evaluated the photosynthetically active radiation transmitted. Plant growth was characterized at the end of 90 days, through morphological measurements: height, stem diameter, leaf area and dry mass of the root partition, shoot and full part, and the ratio of root/shoot. Adopted a completely randomized design (CRD) in factorial 3X4X3 composed of three species (K. anthoteca, K. senegalensis and K. ivorensis), four levels of available soil water (20, 40, 60 and 90%), inserted in three microclimatic conditions (24,7 °C, 0,30 Kpa; 28,6 °C, 0,95 Kpa; 29,8 °C, 1,80 Kpa) with five replications. The sampling unit consisted of one plant per pot. Values were subjected to analysis of variance (ANOVA) to assess possible interactions between the factors species and water levels for each environment separately. The results showed that the growth characteristics of the species of african mahogany were influenced differently in the face of environmental changes and water availability in the substrate. Without water restriction in soil, water near field capacity, K. ivorensis species showed higher initial growth in microclimates studied, however, did not differ from K. senegalensis in the microclimate of higher atmospheric demand (higher temperature and high VPD). Fluid restriction, available water below 40%, affected the early growth of species of Khaya, with no differences between the mahogany studied.